Behind the Scenes : The Google Art Project at the White House. (Academic Video Online, 2012)
Members of the Google Art project and the Google Street View team recently came to the White House to create a new way for people to tour the White House. Take a look at the process that went into creating a 360 degree virtual walk through of the White House public tour.